Peran Penyuluh Perikanan Terhadap Pengembangan Kelompok Pembudidaya Ikan “Morisama” di Desa Jembayan Loa Kulu - Rhizkyliamie Rossantda; Nurul Ovia Oktawati; Komsanah Sukarti (Jurnal Pembangunan Perikanan dan Agribisnis, 2021)
The purpose of this study was to determine the level of the instructor's role in the development of fish cultivator groups in Jembayan Village, Loa Kulu District. The research was conducted for 14 months starting in August 2019 and ending in September 2020. The stages of the research included preparation, data collection, analysis of results, discussion, and final thesis report. This research was conducted in Jembayan Village, Loa Kulu District, Kutai Kartanegara Regency. The role of the instructor consists of four indicators, namely (instructor as a leader, extension as a guide, extension as an organizer and dynamist, extension as a technical). The measurement of the four indicators of the role of extension personnel can be measured using the sampling method used is the census. Data analysis using the quantitative descriptive method with a Likert scale model. Each question item is given a score expressed in integers (1,2,3) according to the choice of the respondent. The results of this study indicate that the role of fisheries instructors in the development of the “Morisama” fish cultivator group can be seen partially and accumulatively. The role of fishery extension agents partially for extension indicators as leaders and as organizers and dynamics is in the medium class interval category. Meanwhile, the instructor's role is as a supervisor and as a technician in the high-class interval category. Accumulatively, the role of fishery extension agents is in the medium category.